Grafting promoted antioxidant capacity and carbon and nitrogen metabolism of bitter gourd seedlings under heat stress - Liang, Le; Tang, Wen; Lian, Huashan; Sun, Bo; Huang, Zhi; Sun, Guochao; Li, Xiaomei; Tu, Lihua; Li, Huanxiu; Tang, Yi (Frontiers in Plant Science, 2022)
Heat stress can limit vegetable growth, and this can lead to constraints on agricultural production. Grafting technologies, however, can be used to alleviate various plant stresses. In this study, the differences in the heat stress impacts and recovery abilities of pumpkin and luffa rootstocks for bitter gourd were analyzed in terms of their antioxidant activity and carbon and nitrogen metabolism. Compared with the un-grafted and self-grafted bitter gourd, which suffered from heat stress at 40 °C for 24 h, heterologously grafted bitter gourd showed higher heat stability of the cell membrane (relative conductivity and malondialdehyde content were reduced), reduced oxidative stress (antioxidant enzyme activity was increased and the reactive oxygen species content reduced), and increased enzyme activity (sucrose phosphate synthase, sucrose synthase, neutral invertase, and acid invertase) and sugar content (soluble sugar, sucrose, fructose, and glucose) in carbon metabolism. The enzyme activity (nitrate reductase, nitrite reductase, and glutamine synthetase) and product content (nitrate and nitrite) of nitrogen metabolism were also found to be increased, and this inhibited the accumulation of ammonium ions. After the seedlings were placed at 25 °C for 24 h, the heterogeneous rootstocks could rapidly restore the growth of the bitter gourd seedlings by promoting the antioxidant and carbon and nitrogen metabolism systems. When luffa was used as rootstock, its performance on the indexes was better than that of pumpkin. The correlation between the various indicators was demonstrated using a principal component and correlation analysis. The luffa rootstock was found to be more conducive to reducing cell damage and energy loss in bitter gourd seedlings caused by heat induction through the maintenance of intracellular redox homeostasis and the promotion of carbon and nitrogen metabolism.